Evolving education development plan strategy for Ondo State (2021)
The problem of high cost of education to both governments and parents, poor quality of school outcome, and declining public funding for education among many others, have continued to impose serious challenges to most state governments over the years. These challenges have the capacity to restrict the provision of quality education delivery, and subsequently limit the human capital stock necessary for overall national development. This underscores the need for government to evolve an enduring education development planning strategy that will address the aforementioned problems. This paper therefore discussed the actionable areas of concern in Ondo state education sector, which include: access to all levels of education, quality of school output, cost and financing, and effective management of the sector. The paper highlights the actions to be taken in order to improve the quantity and quality of education service delivery in Ondo state, Nigeria